PENERAPAN PRINSIP BUSINESS JUDGEMENT RULE DALAM PUTUSAN LEPAS TERKAIT TINDAK PIDANA KORUPSI DIREKTUR KORPORASI - Kuswandi Kuswandi; Yudi Junadi; Aulia Putri (Jurnal Hukum Mimbar Justitia, 2022)
The Business Judgment Rule is a doctrine that protects directors. Often this doctrine is also one of the reasons and protections for directors who do not want to be held criminally responsible. From this background, there are several problem points as follows: (1) How is the principle setting of the Business Judgment Rule in the Indonesian Criminal Justice System? (2) How is the application of the principle of Business Judgment Rule in the accountability of a director who commits a criminal act of corruption? (3) What is the judge's consideration in applying the principle of the Business Judgment Rule in the case of the Corruption Crime in the decision of Case Number 121 K/Pid.Sus/2020?. The approach method that the author uses is normative juridical law research. The results of the discussion, the regulation of BJR is contained in Article 97 paragraph (5) of Law no. 40 of 2007 concerning Limited Liability Companies. Analysis of Judges' Consideration of the Supreme Court on Decision No. 121 K/Pid.Sus/2020, the author agrees that the defendant Karen Agustiawan is free from all lawsuits. The author recommends to PT. Pertamina to file an arbitration claim for compensation through BANI/SIAC to ROC.Ltd Australia.Keywords : Business Judgment Rule, Corruption Crime, Decision.